Hypoxia represses early responses of prostate and renal cancer cells to YM155 independent of HIF-1α and HIF-2α - David Danielpour; Sarah Corum; Scott M. Welford; Eswar Shankar (Elsevier, 2022)
The imidazolium compound Sepantronium Bromide (YM155) successfully promotes tumor regression in various pre-clinical models but has shown modest responses in human clinical trials. We provide evidence to support that the hypoxic milieu of tumors may limit the clinical usefulness of YM155. Hypoxia (1% O2) strongly (>16-fold) represses the cytotoxic activity of YM155 on prostate and renal cancer cells in vitro. Hypoxia also represses all early signaling responses associated with YM155, including activation of AMPK and retinoblastoma protein (Rb), inactivation of the mechanistic target of rapamycin complex 1 (mTORC1), inhibition of phospho-ribosomal protein S6 (rS6), and suppression of the expression of Cyclin Ds, Mcl-1 and Survivin. Cells pre-incubated with hypoxia for 24 ​h are desensitized to YM155 even when they are treated with YM155 under atmospheric oxygen conditions, supporting that cells at least temporarily retain hypoxia-induced resistance to YM155. We tested the role of hypoxia-inducible factor (HIF)-1α and HIF-2α in the hypoxia-induced resistance to YM155 by comparing responses of YM155 in VHL-proficient versus VHL-deficient RCC4 and 786-O renal cancer cells and silencing HIF expression in PC-3 prostate cancer cells. Those studies suggested that hypoxia-induced resistance to YM155 occurs independent of HIF-1α and HIF-2α. Moreover, the hypoxia mimetics deferoxamine and dimethyloxalylglycine, which robustly induce HIF-1α levels in PC-3 ​cells under atmospheric oxygen, did not diminish their early cellular responses to YM155. Collectively, our data support that hypoxia induces resistance of cells to YM155 through a HIF-1α and HIF-2α-independent mechanism. We hypothesize that a hypothetical hypoxia-inducer factor (HIF-X) represses early signaling responses to YM155.